Pengaruh Media Sosial Instagram Terhadap Keputusan Berkunjung Wisatawan Domestik Di Hidden Canyon Beji Guwang, Bali - Anggraeni, Dwi; Sastrawan, I Gede Anom (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2024)
Nowadays conventional media has been overshadowed by digital media. Social media, especially Instagram plays a significant role in digital marketing. Instagram helps to share information worldwide with only one post. It also applies to the tourism sector. Tourism is an essential thing of everyone’s needs in a way to refresh their minds from work. Bali is well known as one of the tourist’s favorite attractions. Hidden Canyon Beji Guwang is one of the hidden gem that is located in Bali. This study aims to examine how Instagram collectively influences the decision to visit Hidden Canyon Beji Guwang, Bali. This research uses a mixed-method, utilizing quantitative and qualitative strategies. The information was collected through perception, literature study, documentation, and surveys. Furthermore, this study was conducted by disseminating surveys to 30 participants by accidental sampling procedure. The result of the study appears that variable X (Instagram) has a significant influence on variable Y (visiting decision). Based on the results, it shows that Instagram features an exceptionally solid association with tourists’ visiting decisions. Keywords: Social Media, Instagram, Visiting decision